Nano-Extract of Epimedium alpinum Preserves Testicular Histology During Levofloxacin Exposure - prof.Dr.Jabbar Abadi Mohammed; prof.Dr.Sukayna Jabbar Mushattat; Eelaf kareem abd ali; Saja Hassan Abdul- Kadhim (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Antibiotics such as levofloxacin are widely prescribed but have been associated with reproductive tissue alterations following prolonged administration. Specific Background: Plant-derived nanomaterials, particularly nano-extracts from medicinal plants, have gained attention due to their bioactive compounds with antioxidant and anti-inflammatory properties. Knowledge Gap: Limited experimental evidence exists regarding the histological response of testicular tissue to concurrent administration of levofloxacin and Epimedium alpinum nano-extract. Aim: This study examined the histological structure of testes in mice treated with levofloxacin and varying concentrations (5 and 10 mg/kg) of Epimedium alpinum nano-extract. Results: Levofloxacin administration for 30 days resulted in seminiferous tubule degeneration, reduced sperm count, and structural disruption, whereas groups receiving the nano-extract alone maintained normal architecture. Co-administration groups demonstrated preservation of seminiferous tubule integrity and improved spermatogenic organization. Novelty: The study provides experimental histological evidence supporting the tissue-preserving role of Epimedium alpinum nano-extract against antibiotic-associated alterations. Implications: These findings highlight the potential application of plant-based nanophytopharmaceuticals as supportive agents in treatments involving antibiotics with reproductive risks.Hightlights: Levofloxacin administration induced seminiferous tubule degeneration and reduced sperm count. Epimedium alpinum nano-extract maintained normal testicular architecture. Combined treatment preserved spermatogenic organization during antibiotic exposure. Keywords: Epimedium Alpinum, Nano-Extract, Levofloxacin, Testicular Histology, Spermatogenesis